Application of Adsorption Microcalorimetry in the Study of Cu(II) Removal Using Magnetic Nanoparticles - Liliana Giraldo; Juan Carlos Moreno-Piraján (Adsorption Science & Technology)
The objective of this study was to explain the synthesis of magnetic polymer adsorbent (FePA) nanoparticles coupled with metal-chelating ligands of N-(2-acetamido)iminodiacetic acid (ADA) and their application for the removal of Cu(II) ions. Nanoparticles of magnetite–polyvinyl acetate (denoted as Fe–PVAC) were synthesized by coating Fe 3 O 4 (magnetite) with PVAC and vinyl acetate (VAC). Several sequential procedures were performed, and the coupling property of ADA was subsequently used to introduce functional groups on the surface of the Fe–PVAC nanoparticles. These sequential procedures yielded the following: magnetite–polyvinyl alcohol, nanoparticles of magnetite–polyvinyl propenepoxide and nanoparticles of magnetite–PVAC–ADA (Fe–PVAC–ADA). An example of the application of Fe–PVAC–ADA was explained by adsorbing Cu(II) ions, which can be chelated by the metal-chelating ligands of ADA in aqueous solution. Batch experiments were performed to determine the kinetics and mechanism of Cu(II) adsorption by the Fe–PVAC–ADA nanoparticles. The adsorption of Cu(II) on Fe–PVAC–ADA was monitored by adsorption microcalorimetry.